Unveiling novel therapeutic mechanisms of Xinfeng capsule: modulating the ALKBH5–m6A–LINC00968 axis to alleviate oxidative stress-driven NETosis in rheumatoid arthritis - Sun, Yue; Li, Yang; Liu, Jian (Frontiers in Immunology, 2025)
BackgroundRheumatoid arthritis (RA) is an autoimmune disease characterized by neutrophil infiltration and synovial hyperplasia. Neutrophil extracellular trap (NET) formation and subsequent oxidative stress-inflammation responses play a critical role in RA pathogenesis. Although m6A RNA methylation and the long non-coding RNA LINC00968 are known regulators in RA, their functions in neutrophils and the mechanisms underlying the therapeutic effect of the traditional Chinese medicine formula Xinfeng Capsule (XFC) remain unclear.MethodsA retrospective clinical study was first conducted involving 2,367 RA patients. Following propensity score matching, the effects of XFC on immune inflammatory markers and liver/kidney safety were evaluated. Subsequently, in vitro mechanistic investigations were performed using RT-qPCR, Western blot, MeRIP-qPCR, CCK-8, flow cytometry, immunofluorescence, and ELISA to assess m6A levels, gene expression, cell proliferation, cell cycle, NET formation, and oxidative stress/inflammatory factors. Molecular docking was used to predict the binding affinity between active components of XFC and ALKBH5.ResultsClinical results demonstrated that XFC significantly improved multiple immunoinflammatory markers in RA patients, including ESR, Hs-CRP, RF, CCP, NLR, and SII, without hepatorenal toxicity. Mechanistically, ALKBH5 was upregulated in the RA microenvironment, leading to reduced m6A methylation and enhanced expression of LINC00968. This axis promoted neutrophil hyperactivation, G1-phase arrest, and NETosis, accompanied by aggravated oxidative stress via the NADP+/NADPH pathway and elevated pro-inflammatory cytokine release (TNF-α, IL-6, and IL-17A). XFC treatment inhibited ALKBH5 activity, increased m6A methylation of LINC00968, and subsequently suppressed neutrophil dysregulation, NET formation, and oxidative stress-inflammation responses. These effects were consistently validated in rescue experiments involving ALKBH5 knockdown and LINC00968 overexpression.ConclusionThis study unveils a novel ALKBH5–m6A–LINC00968 signaling axis that critically regulates neutrophil hyperactivation and NETosis in RA. XFC attenuates the neutrophil–NET–synovial cell inflammatory cascade by targeting ALKBH5 and promoting m6A methylation of LINC00968, providing an epigenetically regulated therapeutic strategy for RA treatment within a traditional medicine framework.